Variações espaciais de propriedades físicas do remanescente de supernova RCW 103 - Sanmartim, David (2008)
Since the observation of the supernova event SN 1987A, observational research on supernova and supernova remnants, including the ones on the optical spectrum, has been much explored. However, most of these studies have been limited to present integrated or punctual data from extragalactic or galactic supernova remnants. The present work has the objective of presenting some physical and kinematic properties from the galactical supernova remnant RCW 103, not limiting itself to punctual measures. Long slit two-dimensional spectra were obtained through spectrophotometric measures with high signal-noise in the range of 6000 to 7000 A, by using the Cassegrain spectrograph attached to 1.6 m telescope of the Observatório Pico dos Dias. With the slit on the East-West direction and with exposure time of 1200~3, the galactical nebula RCW 103 was swept at 14 different declinations, a11 the times with a distance of 5". As a first step, one-dimensional spectra at 4.6" one from each other in right ascension were extracted, allowing the construction of two-dimensional maps of the Ha flux and of the electron density. Maps with a special resolution of 4.6" x 5" for these two physical properties were obtained. As a second step, from the same two-dimensional spectra, spectra with apertures of 2.3" were extracted, from which measures of the center of the Ha line and its width at half maximum were estimated. Based on these two measures, the maps of radial velocity and of the width at half maximum itself were constructed, both of them with resolution around of 2.3" x 5". As a sensor of electron density, the [SII] (X6717/X6731) lines ratio was used, generating an irregular distribution of electron density around 1433 15 ~ m - ~ . At South-East from RCW 103, a region with electron density sistematically higher was observed, maybe a result from the interaction between the shock wave with a molecular cloud. In the radial velocity map, velocity measures from -200 to +I00 kms-', with a mean radial velocity of -22 kms-' in relation to the local standard of rest, were found. Due to the large dispersion velocity in the internal part of the region observed, maps were constructed to show the nebular regions in which the emission lines present two components. The mean velocity dispersion observed was aproximately 76 kms-'. Finally, taking these measures as a referente, it was possible to estimate the kinematic distance of the region observed, its respective mass, as well as the turbulence energy. The distance found corresponds aproximately to 1.75 f 0.08 kpc and the mass, around 3.2 Ma, with the energy associated to the internal movement at about 2.3 x 104' ergs. It is estimated that the mass of the nebula as a whole should be at least three or four times higher than the value presented.